IMS 552: Information System Management. Group Assignment: Perpustakaan Hamdan Tahir (KOHA) / Muhammad Hazim Azahari … [et al.] - Azahari, Muhammad Hazim; Roslan, Indera Syah Iyman; Mohd Nadzri, Muhammad Rifaie; Maidin, Muhammad Rosmaizul (2015)
For this group assignment project we have choose Perpustakaan Hamdan Tahir at University Sains Malaysia Kubang Kerian, Kelantan. We have chosen the system that being used by their library that is Kohar system. Kohar system is a new system that being used by Hamdan Tahir Library. It is because before they used this system, they already have an experience in using two systems that call Phinix system and Ilmu Perdana system. So based on the project and based on the research that we have done, there are a few thing that make the library change their system to Koha. By the way, based from this three system that being used by Hamdan Tahir library, they have their own advantage and disadvantage. Koha system is an open source system. It means this system can be used by public and it’s open to all USM student and staff and they can use this system every time they need. Koha system is a kind of web based. So, it doesn’t need any software to install this system. Koha system serves as a landing page for librarians who are interested the most advanced and cost effective open source automation solution on the market. So, by using this research we know how the Koha system being function and how this system can help student in their study. The system is easy being used by user and the interface of the system is easy to understand by new user. By using this system, we know that, student and staff can access the book or journal that they want by only access by using this Koha system.